EFEKTIVITAS SISTEM INFORMASI PELAPORAN MONITORING DAN EVALUASI (E-CONTROLLING) PADA BAGIAN EVALUASI PEMBANGUNAN SEKRETARIAT DAERAH KOTA BONTANG - Nur Ahsani Maghfiroh (Jurnal Paradigma (JP), 2017)
This study aims to analyze The Effectiveness of The Reporting Monitoring and Evaluation System Information (e-Controlling) on The Development Evaluation Section in The Secretariat of Bontang City Government and to analyze the enabling and preventing factors of The Effectiveness of The Reporting Monitoring and Evaluation System Information (e-Controlling) on The Development Evaluation Section in The Secretariat of Bontang City Government. In this study the author uses descriptive research with qualitative analysis method. The results of this research shows that the Application or The Reporting Monitoring and Evaluation System Information (e-Controlling) has been well implemented as it has loaded the stages in the reporting that makes it easier to implement and present the accountable and real time monitoring and evaluation report